2014
DOI: 10.2169/internalmedicine.53.2419
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypokalemia and Thyrotoxic Paralysis from Painless Thyroiditis Complicated by Life-threatening Polymorphic Ventricular Tachycardia and Rhabdomyolysis

Abstract: A 61-year-old man presented with lower extremity paralysis and severe hypokalemia. His thyroid function test showed thyrotoxicosis. Despite attempts to correct his hypokalemia, he developed pulseless polymorphic ventricular tachycardia two hours later. He was successfully resuscitated after defibrillation. We performed continuous venovenous hemodiafiltration for 10 days due to acute kidney injury and rhabdomyolysis. We observed life-threatening polymorphic ventricular tachycardia requiring urgent defibrillatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…11 Tall P waves, prominent J waves, ST-segment depression, a prolonged QT interval, premature ventricular contraction, ventricular tachycardia, and torsade de pointes can also be observed in patients with hypokalemia. [12][13][14][15][16] In the present case of severe hypokalemia, the ECG showed typical alterations in T waves, U waves, and a prolonged QU interval. Multiple mechanisms contribute to the dynamic morphology of T waves related to hypokalemia.…”
Section: Discussionsupporting
confidence: 49%
“…11 Tall P waves, prominent J waves, ST-segment depression, a prolonged QT interval, premature ventricular contraction, ventricular tachycardia, and torsade de pointes can also be observed in patients with hypokalemia. [12][13][14][15][16] In the present case of severe hypokalemia, the ECG showed typical alterations in T waves, U waves, and a prolonged QU interval. Multiple mechanisms contribute to the dynamic morphology of T waves related to hypokalemia.…”
Section: Discussionsupporting
confidence: 49%
“…In this case, based on the patient's clinical presentation and associated findings, a diagnosis of TPP due to painless thyroiditis was made. Painless thyroiditis presenting with TPP has been rarely reported [7][8][9][10][11]. A literature review revealed only 8 cases of TPP due to painless thyroiditis including our case ( Table 1).…”
Section: Discussionmentioning
confidence: 84%
“…Profound hypokalemia with serum potassium levels of less than 2.5 mEq/L, may cause rhabdomyolysis by reducing blood flow to the muscles in response to exertion [ 21 ]. Hypokalemia is also associated with severe muscle weakness and pain in the setting of thyrotoxic periodic paralysis (TPP) [ 26 ], and in a reported case of TTP, myopathy progressed to the development of rhabdomyolysis [ 27 ]. In our case, the patient had only mild hypokalemia ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%